1535. Utility of CT Abdomen in Evaluation of Neutropenic Fever in Patients with Hematological Malignancies. (26th November 2018) - Al-Ward, Ruaa; Rizvi, Syed Ahsan; Hamdi, Ahmed; Farid, Saira; Sohail, M Rizwan
Abstract: Background: Infections is a serious complication of severe neutropenia and is associated with significant morbidity and mortality. Pan CT scan or CT abdomen is frequently ordered to identify infection source in neutropenic fever. However, utility of CT abdomen in this clinical scenario has not been systematically analyzed. Methods: We retrospectively reviewed all adults hospitalized at our institution with neutropenic fever from January 2006 to December 2016 and had CT abdomen for source identification. Demographic, clinical, imaging, and outcome data were abstracted and analyzed using descriptive statistics. Results: Overall, 156 patients (61.5% males) met the study criteria. The most common underlying hematologic malignancies were leukemia in 83 (53.2%) and malignant lymphoma 46 (29.5%). Others included multiple myeloma, myelodysplasia, and benign hematological malignancies. The most common presenting symptoms, besides fever, at the time of CT abdomen were chills (33.5%), abdominal pain (23.9%), nausea (23.2%), diarrhea (20.6%), cough (19.5%), shortness of breath (12.3%), and skin rash (18.4%). Initial CT abdomen was positive in 45 (28.8%). Repeat CT abdomen was obtained in 22 (14.3%) for persistent fevers and had positive findings for infection source in 85.7%. Sources of infection identified on CT abdomen were involving gastrointestinal tract (46.7%), hepatobiliary system (24.4%), urinary tract (21.1%) and peritoneum (7.8%). In terms of microbiology, a causative organism was identified in blood in 53 (34.9%), urine in 15 (9.9%), stool in 15 (9.9%), and respiratory secretions in 8 (5.3%). Causative pathogens included Gram-positive bacteria in 30 (62.5%), Gram-negative bacteria in 23 (47.9%) and Anaerobes in 5 (10.4%) cases. CT abdomen finding resulted in antimicrobial changes in 75 (59.5%) of patients and procedural intervention in 14 patients (9.3%). Conclusion: While routine use of CT abdomen for evaluation of neutropenic fevers is low yield, CT findings can help identify a source of infection, necessitating change in antimicrobial therapy or procedural intervention, in patients with abdominal symptoms or persistent fever despite broad-spectrum antimicrobial therapy. Disclosures: All authors: No reported disclosures.